Design understanding the elements - Strzelinski, James; Hollaender, Sherri; Roach, John (Insight Media, 2007)
Featuring a professor and students from the Parsons School of Design, this program examines the elements of design. It discusses line; shape, including two- and three-dimensional, geometric, and organic; visual and tactile textures; size; and such color principles as value, hue, complimentary, analogous, triadic, additive and subtractive colors, and primary colors. Examples from fields such as architecture, fashion, interior design, andart are included.